ANALISIS KUALITAS PELAYANAN PADA FASILITAS PENDUKUNG DI FAKULTAS SAINS DAN TEKNOLOGI UIN SUSKA RIAU MENGGUNAKAN METODE SERVICE QUALITY(SERVQUAL) DAN CUSTOMER SATISFACTION INDEX (CSI) - Miza Yuzela; Ismu Kusumanto; Suherman Suherman; Fitriani Surayya Lubis; Muhammad Rizki (Indragiri Islamic University, 2023)
Service quality is one of the most important aspects in an agency, one of which is the facilities on campus. The Faculty of Science and Technology UIN SUSKA RIAU has not fully provided adequate facilities according to student needs so that students are not satisfied with the facility services provided. The purpose of this study is to analyze the quality of service in supporting facilities and provide good service improvement proposals for the future. Based on the results of the study, 12 statement attributes were obtained with five dimensions that could not satisfy students because the quality value of each dimension was smaller than 1 (Q < 1). This research is expected to be an evaluation material for agencies in order to improve the quality of service in the facilities provided.